Achieving the ASEAN Economic Community 2015 challenges for member countries & business - Basu Das, Sanchita (Institute of Southeast Asian Studies, 2012)
ASEAN leaders proclaimed to create an ASEAN Economic Community by 2015. But achieving the target requires cooperation and coordination both within and among the ten ASEAN economies. Currently, with countries having varying considerations towards complete liberalization, protectionism still persists in certain sectors of the economies. Lot of work needs to be done in addressing the domestic reforms, the gaps in infrastructure, the lack of human resources and adequate institutions. Moreover, it is the businesses whose decisions and actions will help the region to achieve an effective integration. The policymakers have vital roles to play in raising the engagement of the private businesses in ASEAN matters. As time is limited, one way for ASEAN is to focus on "core" elements of integration and implement them earnestly in the shortest possible time. The rest of the process, as envisaged in the AEC blueprint, can follow beyond 2015. This book examines the state of readiness of the member countries for regional integration and discusses the challenges to ASEAN businesses. It gives policy recommendations to address some of the issues faced by the key stakeholders.